AI*IA 2017 : Advances in Artificial Intelligence : XVIth International Conference of the Italian Association for Artificial Intelligence, Bari, Italy, November 14-17, 2017, Proceedings /: Advances in Artificial Intelligence : XVIth International Conference of the Italian Association for Artificial Intelligence, Bari, Italy, November 14-17, 2017, Proceedings. (2017) - Unknown
No abstract available